PEMBELAJARAN BRAIN BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN DAN DISPOSISI REFLEKTIF MATEMATIS PESERTA DIDIK - Hardi Kusnandar (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2019)
Brain Based Learning To Improve Students' Mathematical Reflective Capabilities andDispositions. Mathematics Education Study Program, Postgraduate Program at Sultan AgengTirtayasa University. 2019. The purpose of this study was to determine the interaction of BBLlearning on Reflective Abilities and Dispositions Viewed from KAM. The low level of criticalthinking skills will also affect the low ability of reflective thinking in students. Reflectivedisposition is formed from habituation to the learning process carried out by emphasizinglearning reflective abilities. The method used in this study is a quasi-experimental method. Theresults revealed that the ability and disposition of reflective thinking in the class using BBLlearning was better than expository learning; there is no interaction between learning and KAMto increase Mathematical Reflective Capability; there is an interaction between learning andKAM towards increasing Reflective Mathematical disposition.Keywords: Problem-Based Learning, Mathematical Initial Capability, Reflective Capability,Reflective Disposition